Remoção de Carbofurano em Água Empregando Resíduos Agroindustriais como Adsorventes - Tiago dos Santos Estrela; Isaias Alves Rodrigues; Jacques Antonio de Miranda; Valdeilson Souza Braga (Orbital: The Electronic Journal of Chemistry, 2016)
In this study aimed to evaluate the possibility of using industrial boiler ash and rice husk ash in removing the commercial pesticide (carbofuran) in aqueous solution. These solids were collected in the Barreiras/BA, were heat treated and characterized by XRD and FT-IR. The adsorption experiments were performed in batch and the carbofuran removal was quantified using the spectrophotometry in the UV region. XRD data showed high silica content in boiler ash, which was reinforced by FT-IR analyses, showing the band FT-IR associated with presence of silica. In the FT-IR analysis of rice husk ash, this band relative to silica also were observed. The potential of adsorption of the ash industrial boiler and rice husk ash was verified obtaining significant results in the removal of carbofuran at low concentrations (2 mg/L), showing 100% of removal of pesticides from 720 min, used the ash industrial boiler, giving these materials a promising character as adsorbents. In the kinetic study of carbofuran adsorption, the mechanism of pseudo-second-order was better adjusted using the RHA as adsorbent, with a correlation coefficient (R2) of 0.997. The adsorption equilibrium was adjusted better to model of adsorption isotherm of Freundlich with a correlation coefficient of 0.999.DOI: http://dx.doi.org/10.17807/orbital.v1i1.716